1996
DOI: 10.1080/01140671.1996.9513975
|View full text |Cite
|
Sign up to set email alerts
|

Using early‐season measurements to estimate fruit volume at harvest in kiwifruit

Abstract: The results of controlled environment experiments and a field survey covering six major New Zealand kiwifruit (Actinidia deliciosa) growing regions over 3 years showed, surprisingly, that the effect of temperature on the rate of fruit growth is small, at least during the second half of the fruit growth period. The considerable variation in the mean and standard deviation of fruit volume at harvest observed in the field among seasons and sites is therefore not attributable to temperature differences during the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
1
1

Year Published

1998
1998
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 31 publications
1
17
1
1
Order By: Relevance
“…We have yet to identify the factors that determine this variation in fruit size potential; however, it is likely that this potential is established during the early part of the season. Hall et al (1996) have shown that 75% of the variation in fruit volume at harvest is determined by 50 days after flowering. The first 58 days is also the period when most cell division occurs in kiwifruit (Hopping 1976), and thus the amount of cell division during this period may be directly linked to fruit size at harvest.…”
Section: Fruit Size Potentialmentioning
confidence: 99%
See 1 more Smart Citation
“…We have yet to identify the factors that determine this variation in fruit size potential; however, it is likely that this potential is established during the early part of the season. Hall et al (1996) have shown that 75% of the variation in fruit volume at harvest is determined by 50 days after flowering. The first 58 days is also the period when most cell division occurs in kiwifruit (Hopping 1976), and thus the amount of cell division during this period may be directly linked to fruit size at harvest.…”
Section: Fruit Size Potentialmentioning
confidence: 99%
“…Hall et al (1996) reported that c. 75% of the variation in mean fruit volume at harvest was already determined by 50 days after flowering. By this time the majority of cell division has been completed (Hopping 1976) and the second, slower phase of fruit growth is starting although this is only about a third of the way through the fruit growth period.…”
Section: Introductionmentioning
confidence: 99%
“…The low importance of ovary weight (i.e., "starting capital" for fruit growth) across seasons and regions, implies that the differences in fruit size at Day 50 that are found to be highly correlated with fruit size at harvest (Hall et al 1996) are the result of something that happens either: (1) after flowering and during the first 50 days of fruit growth; or (2) before flowering but is not expressed during the first 50 days of fruit growth; or (3) before flowering and is expressed before flowering but was not detected by our measurements.…”
Section: Effects Of Flower Quality On Fruit Weightmentioning
confidence: 99%
“…Hall et al (1996) found that c. 75% of the variation in mean fruit volume and 80% of the standard deviation at harvest were already determined by 50 days after flowering. This is about the time that the second, slower phase of fruit growth starts and is only one third of the way through the fruit growth period.…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation